DI-088 Single-tablet regimen Tenofovir/Emtricitabine/Rilpivirine: one year's experience. (24th March 2015) - De Castro Julve, M; Rudi Sola, N; Estefanell Tejero, A; Oliver Ferrer, E; Ortiz Ruiz, L; Raich Montiu, L; Borràs Trias, L; Pontes García, C; Gorgas Torner, MQ
Abstract : Background: Tenofovir/emtricitabine/rilpivirine (TDF/FTC/RPV) is a recently-marketed fixed-dose combination of antiretrovirals with which there is little clinical experience as yet. Purpose: To describe our clinical experience with TDF/FTC/RPV, in terms of effectiveness, adherence and causes of discontinuation after its first year of use in our hospital. Material and methods: We retrospectively collected data from medical records and the Outpatient Pharmacy Database on all patients who started TDF/FTC/RPV in our centre since its introduction in May 2013, and who had at least one year of follow-up. Baseline and one year viral load (VL) and CD4 counts were recorded for those who completed 12 months treatment with TDF/FTC/RPV. For those who did not, the reason for withdrawal and mean time on treatment were obtained. Adherence was calculated from dispensed and retrieved units, considering the period between dispensing the drugs. Results: 83 patients were treated with TDF/FTC/RPV; 60 male, mean age 45.1 years (SD10.5), 79 had previously received antiretrovirals. Four patients were lost to follow-up. Of 65 patients who completed one year of treatment, 46 of 51 who had undetectable baseline VL remained undetectable, and 12 of 14 patients with detectable baseline VL reached <20 copies/ml. Mean CD4 counts were 646 (SD 254) and 656 (SD 297) cells/mm 3 at baseline and one year, respectively. The average adherence was 92% of the theoretical intake, 75% in the subgroup who had virological failure after 12 months. Treatment with TDF/FTC/RPV was discontinued in 14 patients due to: virological failure (5), side effects (4), drug interactions (3), immunologic failure (1) and desire to become pregnant (1). The average length of treatment of these patients was 6.2 months (range 2.4–11.3 months). Conclusion: TDF/FTC/RPV was effective in terms of VL and CD4 counts in most patients after one year of treatment. Virological failure after 12 months was associated with low adherence. References and/or acknowledgements: Acknowledgments to Department of Pharmacy. No conflict of interest.